Consumption Choices and Earnings Expectations: Empirical Evidence and Structural Estimation - Christian Stoltenberg; Arne Uhlendorff (Tinbergen Institute, 2022)
In this paper, we document that households' consumption expenditures depend on their expected earnings – even after controlling for realized earnings and wealth. To explain this evidence, we develop and structurally estimate a standard-incomplete markets model in which rational households possess private advance information on their future earnings. We find that households are better informed about their future earnings than an econometrician and that individual expectations are more relevant for the consumption choices of households in the left tail of the wealth distribution. Furthermore, households with advance information prefer less progressive earnings taxes.
Keywords: D52; D31; D84; E21; 330; Private information; household consumption; earnings dynamics; incomplete markets; subjective expectations